Molecular characterisation and genetic affinities of Cyclophyllidean cestodes infecting wild rats in Peninsular Malaysia - Mohd Saad, N.; Mohd Zain, S. N.; Sharma, R. S. K.; Omar, H. (Malaysian Society of Parasitology and Tropical medicine, 2022)
Cestode infections is widely reported in rodents, however species identification remains problematic due to the genetic or interspecies variation. Therefore, this study was aimed to verify the Cyclophyllidean parasites recovered from wild rats captured from different forest types using molecular based methods. Maximum-likelihood (ML) and neighbour-joining (NJ) trees were constructed inferred from 18 small subunit nuclear ribosomal RNA gene (18SrDNA) and mitochondrial cytochrome c oxidase subunit one gene (COX1) sequences of cestode worms recovered from 124 individuals from four rat species. Sequences obtained from both Hymenolepis diminuta and Hydatigera parva represents the first records in Malaysia. All the sequences were successfully amplified with product with total length of 205 and 1202 base pairs (bp), respectively. Three cestode species from the Family Hymenolepididae (Hymenolepis diminuta) and Family Taeniidae (Hydatigera parva; Hydatigera taeniaeformis) were successfully characterized using phylogenetic analyses and haplotype networking. Phylogenetic analysis showed that H. diminuta, Hydatigera parva (Hy. parva) and Hydatigera taeniaeformis (Hy. taeniaeformis) formed its own monophyletic clade in 18SrDNA analyses. Results also showed that Hy. taeniaeformis shared the same haplotype group with Hy. taeniaeformis from China (COX1) and linked with Hy. taeniaeformis from Japan (18SrDNA) while the Malaysian H. diminuta clearly formed a separate haplotype and networked with other regions. The Malaysian Hy. parva isolation, on the other hand, appeared to be genetically distinct from the European Hy. parva (Spain) strain, but closely linked to the local isolates. Molecular methods employed successfully improved in the detection of complex species in this group. The findings showed that molecular data can be useful to deeply study intra-specific variation in other cestode worms.